Chemical potential and free energy of nanoconfined water in Newton black films - Di Napoli, Solange Mariel (2018)
In this work we investigate possible approximations to the free energy and chemical potential of water within a Newton black film as a natural nanoconfinement. As a first step we explore the different approximations in a sample of 500 water molecules (bulk water), finding that the overlapping distribution method is the more accurate. For the Newton black film we also calculate the free energy profile of the water molecules along the bilayer normal. We obtain that depending on the position of the water molecule inside the bilayer, the excess chemical potential is lower than that of bulk water, suggesting that a water molecule might be more stable inside the Newton black film than in bulk. A charged semiflexible amphiphilic model and the TIP5P model of water are used in our simulations.